Understanding the Dark Side of Online Reviews on Consumers' Purchase Intentions in E-Commerce: Evidence From a Consumer Experiment in China - Wang, Junbin; Fan, Xiaojun; Shen, Xiangdong; Gao, Yurong (Frontiers in Psychology, 2021)
(1) Background: online review, as an important way of electronic word-of-mouth (eWOM) communication, plays an important role in e-commerce. However, few studies have examined the dark side of online reviews and their effect on consumers’ purchase intentions. Information in-consistency is one of the dark sides that plays a critical role in influencing consumers’ purchase intentions through online reviews; (2) Methods: using a 2 * 2 between-subject design that explores the main effects of the type of information inconsistency (vertical- vs. horizontal-attribute inconsistency) on purchase intention and the moderating effect of product type (search vs. experience product); (3) Results: this study examines whether and how the type of information inconsistency between online recommendations and reviews influences consumer purchase decision-making; (4) Conclusions: the findings show that vertical-attribute inconsistency leads to a lower purchase intention for search products; moreover, both vertical- and horizontal-attribute inconsistencies have no significant effect on purchase intention for experience products.